Spatial Analysis of the Land Object of Agrarian Reform Redistribution Priorities for Supporting Low Carbon Development - Magfoedin, Moefid; Soemarno, Soemarno; Atikawati, Dini (BHUMI: Jurnal Agraria dan Pertanahan, 2025)
Abstract: This study analyzes the spatial classification of redistribution priorities for Land Objects of Agrarian Reform (TORA) in Non-productive Convertible Production Forest (HPK Non-Productive) covering 14,310.42 hectares in Sintang Regency, West Kalimantan. The land was verified through the Inventory of Land Tenure, Ownership, Use, and Utilization (IP4T) in 2021 and proposed for forest release in 2022. The results of the study show the persistence of Dayak cultural traditions and reveal three key irregularities: landholdings exceeding the 5 ha TORA ceiling, multiple landholdings by single subjects, and the conversion of land to oil palm. Using a mixed-methods approach combining quantitative, qualitative, and spatial analysis with ArcGIS, the study identified three redistribution priorities: (1) fully eligible parcels (≈1.9%), (2) parcels under 5 ha requiring subject verification (≈26%), and (3) parcels over 5 ha, including forest-use and oil palm areas, requiring stricter screening and conflict resolution (≈71%). The LCDI-based analysis estimates 988,800 tC (3.63 million tCO₂e), with rubber plantations contributing >80%. The study recommends an inclusive TORA scheme that accommodates Dayak customary values by allocating communal forests (hutan ulayat, tana ulen, tana jaka) within each village. This supports forest cover preservation while aligning with the FOLU Net Sink policy, the Low Carbon Development Initiative (LCDI), and the oil palm moratorium, thereby reinforcing sustainable agrarian reform in forest boundary regions. Keywords: Forest Boundary, Incremental Agrarian Arrangement, Low Carbon Development, Non-Productive HPK, TORA Redistribution.